Enhanced cycling stability and reduced hysteresis of AB5-type hydrogen storage alloys by partial substitution of Sn for Ni. (26th June 2022) - Xu, Jie; Chen, Xiangyu; Zhu, Wei; Zhang, Weirong; Cui, Han; Zhu, Siqi; Liu, Jingjing; Liu, Hongfei; Yan, Kai; Cheng, Honghui
Abstract: Rare-earth AB5 -type alloys have been widely studied due to their great application potential in gaseous hydrogen storage, but their overall hydrogen storage properties still need to be further improved for more extensive applications. In this work, the effect of Sn partial substitution for Ni on the plateau characteristics and cycling performance of the LaNi5- x Sn x ( x = 0, 0.25, 0.5, 0.75, 1) alloys are systematically studied. It is found that the segregation effect caused by Sn addition leads to the multi-CaCu5 phase structure with different cell parameters which may have a positive effect on stabilizing the alloys' structure during cycling by playing a buffer role. Also, the replacement of Sn element results in a higher anisotropic c/a value, which reduces microstrain and improves the cycle life. The capacity retention after 1000 cycles increases from 83.2% ( x = 0) to 95.8% ( x = 0.75). Moreover, the addition of Sn significantly reduces the hysteresis of the alloys from 0.212 ( x = 0) to 0.023 ( x = 0.5) at 383 K, owing to the reduction of the microstrain during hydrogen absorption/desorption. Graphical abstract: Image 1 Highlights: Hydrogen storage properties of LaNi5- x Sn x alloys within 1000 cycles are studied. Multiple CaCu5 phases are induced by Sn addition. Hysteresis is dramatically decreased by Sn addition. Long-term cycling performance is significantly improved by Sn addition. The novel result is the extension of the previously studied composition range.